2020
DOI: 10.1101/2020.11.27.401398
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single-cell transcriptomics of the early developing mouse cerebral cortex disentangles the spatial and temporal components of neuronal fate acquisition

Abstract: In the developing cerebral cortex, how progenitors that seemingly display limited diversity end up in producing a vast array of neurons remains a puzzling question. The prevailing model that recently emerged suggests that temporal maturation of these progenitors is a key driver in the diversification of the neuronal output. However, temporal constrains are unlikely to account for all diversity across cortical regions, especially in the ventral and lateral domains where neuronal types significantly differ from … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 84 publications
(123 reference statements)
0
6
0
Order By: Relevance
“…Several initial studies performed bulk RNA-sequencing on the embryonic ventral forebrain, but these studies were not able to differentiate molecular characteristics between progenitor domains (Tucker et al, 2008;Zechel et al, 2014). More recent studies performed comprehensive scRNAseq experiments on the developing neocortex, but they did not focus on the ventral telencephalon or interneuron development (Di Bella et al, 2021;Loo et al, 2019;Moreau et al, 2021;Telley et al, 2019;Telley et al, 2016). scRNAseq studies that targeted GEs found that initial signatures of mature interneuron (IN) subtypes appear in postmitotic precursors whereas very little transcriptional diversity was detected in VZ and SVZ progenitors (Chen et al, 2017;Mayer et al, 2018;Mi et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Several initial studies performed bulk RNA-sequencing on the embryonic ventral forebrain, but these studies were not able to differentiate molecular characteristics between progenitor domains (Tucker et al, 2008;Zechel et al, 2014). More recent studies performed comprehensive scRNAseq experiments on the developing neocortex, but they did not focus on the ventral telencephalon or interneuron development (Di Bella et al, 2021;Loo et al, 2019;Moreau et al, 2021;Telley et al, 2019;Telley et al, 2016). scRNAseq studies that targeted GEs found that initial signatures of mature interneuron (IN) subtypes appear in postmitotic precursors whereas very little transcriptional diversity was detected in VZ and SVZ progenitors (Chen et al, 2017;Mayer et al, 2018;Mi et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, suggesting of possible synergic role of Dbx1 and Pcdh8 in cell identity determination. Indeed, Pcdh8 KD in Dbx1 EE cells reversed induction of Nr4a2 expression supporting that Pcdh8 is in part responsible for Nr4a2 expression and SPlike phenotype of Dbx1-derived lineages (Arai et al, 2019;Moreau et al, 2021). Moreover, further analysis showed the action of Pcdh8 KD on downregulation (Dbx1 EE + Pcdh8 KD) and upregulation (Pcdh8 EE) of Dbx1, thus pointing to Pcdh8 as a post-transcripitional modulator of Dbx1 expression.…”
Section: Adhesion Is An Important Component Of the Cell Identitymentioning
confidence: 79%
“…To better appreciate the possible implication of such candidates downstream of Dbx1 we used scRNAseq. We first used a previously generated dataset sampling cell diversity around the pallialsubpallial boundary (PSB) at E12.5 (Moreau et al, 2021). We found Cdh2, Pcdh9 and Pcdh19 broadly expressed, with no specific enrichment (https://apps.institutimagine.org/mouse_pall ium/).…”
Section: Pcdh8 and Dbx1 Show Sequential Or Concomitant Expression Res...mentioning
confidence: 99%
See 2 more Smart Citations